Partisipasi Masyarakat dalam Pembentukan Peraturan Daerah di Kabupaten Minahasa Selatan - Siar, Lendy; L. Lambonan, Marthin; Pondaag, Audi Helri (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This research is useful for finding a model for institutionalizing community participation in the formation of regional regulations in South Minahasa Regency (KMS) so that they comply with the principles of forming good laws and regulations but can be accepted and implemented by the community. Data collection began with extracting legislative literature regarding its formation, both national, provincial and local government. Interviews involved informants from members of the Regional People's Representative Council (DPRD) and local government officials who were selected using purposive sampling. The formation process relies on proposals from the regional government and the DPRD's initiative. In this way, for the community, there is room for participation but it is not institutionalized, so it is passive at every stage. Such conditions are not in line with the principles of forming laws and regulations in the Republic of Indonesia.